Tissue Staining (Chromoscopy) of the Gastrointestinal Tract - M Brian Fennerty (Canadian Journal of Gastroenterology)
Tissue staining, or chomoscopy, is used as an adjunctive technique during gastrointestinal endoscopy. Chemical agents are applied to the gastrointestinal mucosal surface to identify specific epithelia or to enhance the mucosal surface characteristics of the gastrointestinal epithelium. This aids in the recognition of subtle lesions (ie, polyps) or allows directed targeting of biopsies (ie, sprue or Barrett’s esophagus) to increase the yield of endoscopic diagnostic accuracy. The four endoscopic tissue-staining techniques in use are vital staining, contrast staining (chromoscopy), reactive staining and tattooing. Some of the agents used for endoscopic tissue staining and the uses of chromoscopy in identifying pathology of the esophagus, stomach, small bowel and colon during endoscopy are discussed.